1982
DOI: 10.1093/oxfordjournals.jbchem.a134075
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in Heat Capacity and Entropy of Troponin C Induced by Calcium Binding1

Abstract: We have used the method of enthalpy titration to analyze the structural changes of troponin C caused by calcium binding. Successive additions of calcium to metal-free troponin C in a microcalorimeter cell result in at least three distinguishable transitions. Analysis of the results has shown that troponin C has at least three classes of calcium binding sites; one site of highest affinity (binding constant, 10(8)-10(10) M-1), one site of next highest affinity (binding constant, 10(6)-10(7) M-1) and two low affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…In the case of the C-terminal domain of TnC, AGO has also been measured calorimetrically for the binding of 2 calcium ions (Potter & Gergely, 1975;Yamada, 1978;Yamada & Kometani, 1982;Imaizumi et al, 1987). Although studies for rabbit TnC are not so clear, a AGO = -85 kJ/mol was obtained for bullfrog TnC (Imaizumi et al, 1987), which is in excellent agreement with the AGO derived from dissociation constants (Table 1).…”
Section: Comparison Of a G F O With Ago From Calcium Dissociation Consupporting
confidence: 66%
“…In the case of the C-terminal domain of TnC, AGO has also been measured calorimetrically for the binding of 2 calcium ions (Potter & Gergely, 1975;Yamada, 1978;Yamada & Kometani, 1982;Imaizumi et al, 1987). Although studies for rabbit TnC are not so clear, a AGO = -85 kJ/mol was obtained for bullfrog TnC (Imaizumi et al, 1987), which is in excellent agreement with the AGO derived from dissociation constants (Table 1).…”
Section: Comparison Of a G F O With Ago From Calcium Dissociation Consupporting
confidence: 66%
“…Titrations with Ca2+ (or Mg'+) were performed by the successive addition of a small amount (4.1 pl) of 25 mM CaC12 (or 50 mM MgC12) solutions from a titration apparatus mounted on the outside of the calorimeter block [24,25]. The calorimeter cell contained 5 ml of 0.1-0.18 mM parvalbumin, 100 mM KC1 and 20 mM piperazine-ZV,N'-bis(2-ethanesulfonic acid) (Pipes)-NaOH (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%
“…Further details of the calorimetric titrations are given in [25-271. To obtain the heat attributable to Ca2+ (or Mg2+) binding, the observed heat must be corrected for the heat caused by the interaction between the Pipes buffer and protons released when Ca2+ (or Mg2+) binds. The latter was determined as in [22,25]; it was less than 0.05 mol/mol binding site. The observed enthalpy changes were not corrected, since the heat actually produced by the pro-78 tons released was negligible, taking the enthalpy change of the protonation of Pipes as -11.46 kJ/mol [28,29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rabbit skeletal muscle the characteristic phase of positive enthalpy and heat capacity changes is associated with calcium binding to one of the two high-afifinity calcium sites of the C-terminal domain (Yamada and Kometani, 1982). Calorimetric studies have also shown that, in frog skeletal troponin C, one of the N-terminal low-affinity calcium-binding sites is the "active" calcium site (Imaizumi and Tanokura, 1990).…”
Section: Microcalorimetric Approach To the Calchjm Binding Of Troponimentioning
confidence: 99%